Intelligent controller based energy management for stand‐alone power system using artificial neural network. (9th August 2020) - Boujoudar, Younes; Azeroual, Mohamed; El Moussaoui, Hassan; Lamhamdi, Tijani
Summary: Standalone Power Systems (SPS), formerly known as Micro Power Systems, is an off‐grid electricity system for locations that are not fitted with an electricity generation. Typical SPS include one or more renewable electricity sources, energy storage, and regulation. In this paper, supervision of hybrid Photovoltaic system and battery storage is presented. The power balance of the hybrid system is made on an intelligent supervisor based on Artificial Neural Network Controller (ANNC). The main purpose of this paper is the control of DC/DC Bidirectional Converter (DBC), which connect the Li‐ion battery with the DC_Bus of Stand‐alone Power Systems (SPS). Based on the use of artificial neural network controller, which are effective tools for highly nonlinear system. The proposed technique does not require a pre‐defined model of power DBC only depend on power and voltage system data. Simulation for stand‐alone systems performed at Matlab Simulink. The comparison with PID controller for the result obtained of DC_Bus voltage, and power demanded, demonstrate the robustness, and satisfactory performance of the proposed control strategy. Abstract : The main purpose of this paper is the control of DC/DC Bidirectional Converter (DBC) using artificial neural network controller. The BDC manage the charging/discharging of the battery, and connect the Li‐ion battery with the DC_Bus of Stand‐alone Power Systems (SPS) in order keep the energy balance at the DC_BUS.